OPTIMASI DESAIN GAS LIFT DENGAN SUPLAI GAS UNLIMITED PADA PENGEMBANGAN LAPANGAN "PSI" SECARA TERINTEGRASI DENGAN MENGGUNAKAN ECONOMIC SLOPE - Leonardo, Stephen
Artificial lift is methods used to lower the well flowing pressure in order to obtain higher production rate from the well. Gas lift is one of the artificial lift methods commonly used in the world. Gas lift is the injection of gas into the well to reduce the fluid density. Consequently, pressure gradient in the wellbore will decrease and fluid will be easier to be lifted to the surface. Reservoir in field “PSI” is multilayer and has edge water drive as the driving mechanism. As the production duration goes by, the wells in this reservoir will have increasing water production. Higher water density will inhibit the natural lifting of the fluid. Therefore, continuous gas lift design will be studied. Gas availability in this study is considered to be unlimited, which there is gas supply that can be buy from outside of the field. With abundant supply of injection gas, one of the considerations in gas lift design is the optimum gas injection rate. Technically optimum gas injection rate is obtained when slope at Gas Lift Performance Curve (GLPC) is equal to zero. But in reality, technically optimum gas injection rate does not necessarily give the optimum revenue economically. In this study, approach using economic slope will be implemented to obtain economically optimum gas injection rate. Then, comparisons with technically optimum gas injection rate will be made. The field development in this study will be done in integrated way from reservoir, surface facilities till evaluation of projects’ economy in effort to simulate the real condition in the field.